Performance Analysis of Downlink-NOMA Over Málaga Distributed Optical Links - Aslan, Kardes; Gucluoglu, Tansal (SPRINGER, 2024)
Non-orthogonal multiple access (NOMA) can be a desirable method since it can utilize resources efficiently to provide larger capacity. Similarly, optical transmission is also becoming popular due to the availability of licence-free large bandwidth and low-cost transceiver implementation. Although optical NOMA system can be promising for long range wireless systems, investigation of its reliability performance is essential for different channel models. In this study, outage probability, channel capacity, symbol error rate expressions, diversity and coding gains for arbitrary number of users are obtained for downlink-NOMA over free space optical links modeled with M & aacute;laga distribution. Theoretical results are verified by numerical examples for various scenarios providing useful background for future analyses and designs.
Keywords: NOMA; FSO; M & aacute; laga turbulence channel; Outage probability; Channel capacity; Symbol error rate; NONORTHOGONAL MULTIPLE-ACCESS; SUBCARRIER INTENSITY MODULATION; COMMUNICATION-SYSTEMS; TURBULENCE CHANNELS; 5G SYSTEMS; ERROR RATE; BER; QAM; Telecommunications